The Cambridge encyclopedia of historical performance in music - Lawson, Colin 1949-; Stowell, Robin 1949- (Cambridge University Press, 2018)
Recent decades have seen a major increase of interest in historical performance practice, but until now there has been no comprehensive reference tool available on the subject. This fully up-to-date, illuminating and accessible volume will assist readers in rediscovering and recreating as closely as possible how musical works may originally have sounded. Focusing on performance, this Encyclopedia contains entries in categories including issues of style, techniques and practices, the history and development of musical instruments, and the work of performers, scholars, theorists, composers and editors. It features contributions from more than 100 leading experts who provide a geographically varied survey of both theory and practice, as well as evaluation of and opinions on the resolution of problems in period performance. This timely and ground breaking book will be an essential resource for students, scholars, teachers, performers and audiences
Keywords: Historische Musikpraxis; Performance practice / History / Encyclopedias; Music / Performance / Encyclopedias; Wörterbuch